Development of ester-based drilling fluids for wellbore enhancement - Ismail Jassim, Lina (2015)
Ester-based drilling fluid has been accepted as an alternative to mineral oils in drilling applications and currently being usedin oil or gas wells exploration around the world. However, the ester has many deficiencies such as high kinematic viscosity andpoorthermal and oxidative stabilities whichlimit its ability to carry and transfer drilled solids under high pressure and high temperature wells. Thus, the main aim of the study is to overcome these limitations by developing the high performance ester-based drilling fluids for deep and ultradeep wells that operate under high pressure and high temperature conditions. The low pressure technology was applied in the synthesis of the ester to minimize ester hydrolysis and thermal instability issues during the drilling operation. The rapid ester synthesis involved the reaction between2- ethylhexanol and vegetable oil-based methyl esters C8-12 in the presence of sodium methoxide as the catalyst. In order to obtain the optimum synthesis conditions, a response surface methodology (RSM) was appraised based on the central composite design. The product with 77 wt. % 2-EH C12 ester content wasobtainedfrom both RSMmodel and experimental data. The 2-EH C12 ester exhibited properties similar to the commercial ester, i.e. kinematic viscosity of 5.2 mm2/sec at 40°C and 1.5 mm2/sec at 100°C, specific gravity of 0.854, 170°C flash point, and -7°C pour point. While the properties of 2-EH C8/10 ester base oil were 3.2 and 1.2 mm2/sec of kinematic viscosity at 40 and 100°C respectively, 80°C flash point, and -15°C of pour point. Various conventional, micro and nano-ester-based drilling formulations were prepared and characterized based on the API Recommended Practice 13B-2. Calcium carbonate (CaCO3) of 5 μm particles, commercial graphene (powder and platelets) and carbon nanosphere (produced in house) nanoparticles have been used as the rheology enhancer and fluid loss agent in geothermal drilling fluid formulation.The performances of 2-EH ester-based drilling fluids were assessed under different hot rolling temperatures (121, 135, 149, 177, 212 and 232oC) for 16 hours. The improvement in both thermal and hydrolytic stability of the synthesized 2-EH C8-12 esters may be due to the unique transesterification method using methyl ester route as opposed to the conventional fatty acids route.Furthermore,the addition of only 0.1wt% of graphene (powder type) to the formulation enhanced further the ester-based drilling fluid performances. The stability of the fluid to plug 10 μm of formation size was evidenced when only 8 ml of filtration and 775 mDarcy of permeability was obtained using (533.4/50.8 × 25.4/101.6) mm ceramic disc. In this study, simulation of conventional and nano-ester-based drilling fluids in eccentric, dual phase flow through horizontal well was performed with the help of three dimensional CFD, Fluent package. The simulation was successful and demonstrated the capabilityof 2-EH ester based drilling fluid to carry and transfer cutting particles of 3, 4.45 and 7 mm sizes in a highly eccentric annular flow of 0.8 eccentricities. The critical fluid velocity that demonstrated the fluid ability to carryand transport cuttings without cuttings bed was at 2.86 m/s. These results confirmed that 2-ethylhexyl ester-based drilling fluids have the potential to be commercialized and used in deep and ultra-deep wells without sagging, pipe sticking, and wellbore instability issues.